Mechanical properties of underwater friction stir welded 2219 aluminum alloy - 刘会杰 张会杰 黄永宪 于雷 (Transactions of Nonferrous Metals Society of China, 2010)
Underwater friction stir welding of 2219 aluminum alloy was carried out in order to further improve the joint performances by varying welding temperature history. The results indicated that the tensile strength of the joint can be improved from 324 MPa by external water cooling action in normal to 341 MPa. However, the plasticity of the joint is deteriorated. The underwater joint tends to fracture at the interface between the weld nugget zone and the thermal mechanically affected zone on the advancing side during tensile test, which is significantly different from the normal joint.